The predictive effect of problematic behaviours on cognitive tempo and attention level in 60-66 months old children - Keskinkilic, Aysegul Ulutas; Emre, Oguz; Cosanay, Burcu (Routledge Journals, Taylor & Francis Ltd, 2021)
This study aimed to investigate the predictive effect of problematic behaviours on cognitive tempo and attention level of 60-66 months old children attending preschool education institutions. The research data were obtained from 155 children between 60 and 66 months old attending independent kindergartens affiliated to the Ministry of National Education in Malatya city centre in 2018-2019 academic year. Regression analysis was performed to examine the mediating role; Bootstrap analysis was used in order to determine direct and indirect path coefficients in regression models. As a result of the findings obtained from the study, while the cognitive tempo of the children included in the sample had a significant effect on attention, there was no significant effect of the cognitive effect on the mediating variables, and the mediating variables on the attention. Therefore, it is seen that behavioural problems do not have a significant role in the effect of cognitive tempo on attention.
Keywords: Preschool; problematic behaviour; cognitive tempo; Preschool-Children; Style; Skills